Study on the Factors Affecting the Quality of Trench Cutting Remixing Deep Wall in Qingdao Area. (22nd February 2021) - Jiang, Peng; Gui, Dazhuang; Wang, Lina; Wang, Hongchao; Zheng, Shijie
Abstract : As a new type of waterproof curtain, several station construction of Qingdao Metro Line 1 successfully used the trench cutting remixing deep wall (TRD). It is difficult to find the factors that affect the wall quality because the method is in situ underground excavating and mixing. This paper has obtained the main factors affecting the TRD quality in Qingdao by studying construction experience and carrying out tests. Geological conditions are fundamental factors. Among them, the parameters of medium-coarse sand layer, the groundwater table, and the humus content are the main factors. The design parameters are the key to high-quality TRD. In the design parameters, the depth inserting into the bedrock, the cement soil ratio, and the mixing time are important factors. And this paper proposes the methods of improving the wall quality, which can provide a theoretical guarantee for the follow-up application of the TRD in the Qingdao area.